2020
DOI: 10.1002/cpt.2046
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19: A Catalyst to Accelerate Global Regulatory Transformation

Abstract: A global crisis the magnitude of coronavirus disease 2019 (COVID-19) can transform drug development and review. It has exposed vulnerabilities and inadequacies in the global healthcare ecosystem as well as spurred innovation, rapid adaption of novel solutions, and unprecedented collaboration among global regulatory agencies, sponsors, and researchers. For the continued and future benefit of patients, it is imperative that all stakeholders leverage the solutions, learnings, and momentum catalyzed by this crisis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…To address the effects of COVID-19 and to simultaneously ensure the continuity of development of non-COVID treatments, regulators have demonstrated significant regulatory agility while maintaining high standards of quality, tolerability, and effectiveness. 1 Regulators have adopted and made public crucial steps to raise awareness and to provide guidance to stakeholders on how to respond and navigate the current pandemic. In doing so, they have demonstrated tremendous agility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the effects of COVID-19 and to simultaneously ensure the continuity of development of non-COVID treatments, regulators have demonstrated significant regulatory agility while maintaining high standards of quality, tolerability, and effectiveness. 1 Regulators have adopted and made public crucial steps to raise awareness and to provide guidance to stakeholders on how to respond and navigate the current pandemic. In doing so, they have demonstrated tremendous agility.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present several documents or informational materials related to the regulatory environment around the development and management of medical products concerning the COVID-19 pandemic. Some of these documents refer to actions, initiatives, or exceptional approaches where health or regulatory authorities have either: (1) advanced existing initiatives aimed at agile and responsive regulatory systems and processes; or (2) introduced new and innovative ways to expedite and improve such processes. For the purpose of this review, we refer to regulatory agility as the willingness of authorities to take quick action within the accepted regulatory framework to ensure that the regulatory ecosystem swiftly responds to the challenges imposed by the pandemic for the ultimate benefit of patients and society as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have argued for applying “regulatory flexibility” beyond the current COVID‐19 pandemic and against a return to previous practices, for the benefit of patients suffering from (life‐threatening) diseases 33,40–42 . This study has shown that regulators have readily accepted telemedicine visits, enhanced remote CT monitoring, DtP IMP supply, and simplified interaction with the authorities via digital means during the pandemic, albeit temporarily.…”
Section: Discussionmentioning
confidence: 84%
“…Other authors have argued for applying "regulatory flexibility" beyond the current COVID-19 pandemic and against a return to previous practices, for the benefit of patients suffering from (life-threatening) diseases. 33,[40][41][42] This study has shown that regulators have readily accepted telemedicine visits, enhanced remote CT monitoring, DtP IMP supply, and simplified interaction with the authorities via digital means during the pandemic, albeit temporarily. However, country-specific differences in the guidance provided within the European Union (mainly regarding regulatory management, DtP IMP supply from the sponsor, and rSDV; Table S3) could have made it difficult for sponsors to adapt to these guidances for trials conducted in multiple MSs.…”
Section: Implications Of This Studymentioning
confidence: 79%
“…New systems could accommodate new forms of evidence from non-traditional sources such as real-world evidence (eg, patient electronic health records and patient experience data) and apply tools such as machine-based learning and artificial intelligence. 16 Although this is a long-term journey and initially will be pioneered by more well-resourced regulators, the hope is that such a system can be designed to be scalable for use by all regulators and so the anticipated benefits of streamlined processes, reduced redundancy and rework, and enriched regulatory decision making will ultimately benefit all patients globally.…”
Section: Digital As a New Regulatory Mainstaymentioning
confidence: 99%